The Effect of McFarland’s Strategy on the Literary Fourth-graders’ Achievement in History - Ahmed, Mohammed Mustafa (Journal of Tikrit University for Humanities, 2024)
The researcher used a strictly controlled experimental design. The researcher chose the fourth literary grade at Al-Mughira Bin Shu’bah Middle School, affiliated with the Anbar Education Directorate, which is represented by Section (B) to represent the experimental group taught according to McFarland’s strategy, and Section (A) represented the control group taught in the traditional way. The number of students was (60), with (30) students in each section. The two groups were rewarded on the variables: the chronological age of the students in months and intelligence. The researcher prepared the research tool for the achievement test. The validity and stability of the tool were verified. The T-test was used to process the data. The results showed the superiority of the experimental group that studied according to McFarland’s strategy in Collection, and the researcher recommended several recommendations and proposals.